2022
DOI: 10.21037/tcr-22-627
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the risk factors of surgical site infection in patients with colorectal cancer

Abstract: Background Surgical site infection (SSI) influenced the result of surgical treatment, which was known as the second most prevalent hospital-based infection. But, the factors of SSI are not uniform. The purpose of this study was to identify the risk factors of SSI in patients with colorectal cancer. We conducted a meta-analysis of epidemiological research to provide a scientific basis for the prevention of SSI. Methods The PubMed, Medline, Embase, China National Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…However, additional studies are still required to demonstrate these prospective associations and to associate the impact of a stoma with the consequences studied. This was suggested also in previous similar meta‐analyses study which showed similar promising outcomes 25 , 26 , 27 , 28 Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different ages, gender, ethnicity, and other variants of subjects; since our meta‐analysis study could not answer whether different gender, ages, and ethnicity are related to the results.…”
Section: Discussionmentioning
confidence: 68%
“…However, additional studies are still required to demonstrate these prospective associations and to associate the impact of a stoma with the consequences studied. This was suggested also in previous similar meta‐analyses study which showed similar promising outcomes 25 , 26 , 27 , 28 Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different ages, gender, ethnicity, and other variants of subjects; since our meta‐analysis study could not answer whether different gender, ages, and ethnicity are related to the results.…”
Section: Discussionmentioning
confidence: 68%
“…54 55 Both superficial and deep/organ space infections are associated with smoking. 38 45 47 56 57 58 Smoking is also associated with increased risk of skin flap necrosis in mastectomy, recurrence after groin hernia repair, wound disruption in plastic surgery and head and neck surgery, and incisional hernia formation. 59 60 61 62 Wound healing in orthopaedic surgery is impaired, with smokers experiencing higher rates of bone nonunion, delayed union, and delayed healing with prosthetic implants.…”
Section: Risks Of Smoking In the Perioperative Periodmentioning
confidence: 99%
“…The NNIS risk index components (ASA anesthetic risk score, Altemeier contamination class, duration of the operation, 3 and emergency versus elective) were recovered from the operative room database which is separated from the HDD. 10 These 6 comorbidities were selected according to literature review: arterial hypertension, 14,19 diabetes, [11][12][13][14][15] cancer, 16,17 immunosuppression, 18 malnutrition, 19 and obesity. 12,19 They were directly extracted from the HDD using defined International Classification of Diseases Tenth Revision (ICD-10) codes, as well as age, sex, length of preoperative stay, and outpatient surgery.…”
Section: Risk Factorsmentioning
confidence: 99%